"Macbeth" in Nineteenth-Century Bengal: A Case of Conflicted Indigenization - Chaudhury, Sarbani; Sengupta, Bhaskar (Multicultural Shakespeare: Translation, Appropriation and Performance, 2013)
Adaptation, a complex bilingual and bicultural process, is further problematised in a colonial scenario inflected by burgeoning nationalism and imperialist counter-oppression. Nagendranath Bose’s Karnabir (1884/85), the second extant Bengali translation of Macbeth was written after the First War of Indian Independence in 1857 and its aftermath – the formation of predominantly upper and middle class nationalist organisations that spearheaded the freedom movement. To curb anti-colonial activities in the cultural sphere, the British introduced repressive measures like the Theatre Censorship Act and the Vernacular Press Act. Bengal experienced a revival of Hinduism paradoxically augmented by the nationalist ethos and the divisive tactics of British rule that fostered communalism. This article investigates the contingencies and implications of domesticating and othering Macbeth at this juncture and the collaborative/oppositional strategies of the vernacular text vis-à-vis colonial discourse. The generic problems of negotiating tragedy in a literary tradition marked by its absence are compounded by the socio-linguistic limitations of a Sanskritised adaptation. The conflicted nature of the cultural indigenisation evidenced in Karnabir is explored with special focus on the nature of generic, linguistic and religious acculturation, issues of nomenclature and epistemology, as well as the political and ideological negotiations that the target text engages in with the source text and the intended audience.